Prevalence of HIV/HBV, HIV/HCV and HBV/HCV Co-infections among Drug Users in a Tertiary Care Public Hospital - Atif, Malik M; Ayub, Sumaira; Asif, Aftab (Journal of Pakistan Psychiatric Society, 2019)
Objective: To find out the prevalence of HIV/HBV, HIV/HCV and HBV/HCV Co-infections among the drug users in a tertiary care public hospital. Study Design: descriptive study. Place and Duration: The study was conducted for a period of 1 year in Drug Addiction Treatment, Rehabilitation and Counseling Center, Department of Psychiatry and Behavioural Sciences, Mayo Hospital, Lahore. Subjects and Methods: A total of 453 drug users admitted in drug addiction ward from August 2016 to July 2017 participated in the study. The study included an interview and blood testing. The questionnaire covered demographic characteristics as well as risk factors. Additionally three types of blood screening tests including Unigold, Determine and Bioline were used. Of 453 drug users 51 (11.3 %) did not get screened and left hospital uninformed as LAMA. Therefore their data was discarded. Results: Out of 402 drug users, 394 (98%) were male and 8 (2%) were female. The age range of the participants was 16-66 years with mean age of 32.2+8.9 years old. About 343 (85.3%) were belonging to low socioeconomic status and 143 (35.6%) had previous history of imprisonment. 235 (58.5%) patients consisted of those who have been using drugs for five years or less while 82 (20.3%) have been using drugs for a period between 11 to 15 years. Among 402 patients, 85 (21.1%) drug users were HIV positive, 13 (3.4%) were Hepatitis B infected and 135 (34.0%) were Hepatitis C positive. Conclusion: Co-infections were prevalent among drug users especially in those who took drugs through injections.